Evaluasi Perkerasan Landasan Pacu Pada Bandara Pattimura Dengan Membandingkan Metode FAA dan FAARFIELD Software - Mario Stevano Lewa; Putu Ariawan; Putu Budiarnaya (Universitas Pendidikan Nasional, 2020)
Maluku is one of the provinces in eastern Indonesia which is famous for its natural beauty. This is supported by the number of tourists who come there through Pattimura airport. With the increasing demand for air transportation at Pattimura airport at this time it is necessary to change the airport facilities specifically runways to accommodate all flight requests. Therefore, the thickness of the pavement of the runway must meet the strength of the structure so that it can serve the movement of the aircraft according to the age of the plan (in 2037). The purpose of the final assignment is to evaluate the strength of the pavement of the runway by comparing the flexible pavement design between the FAA Method and FAARFIELD Software. The data used are passenger data for 2011-2017, aircraft movement data, and runway layout images. Both of these methods will later be used as a reference in changing the thickness of the pavement according to the current condition of the existing runway. The total calculation results using a flexible pavement planning curve with CBR 6 for subgrade and CBR 20 for the subbase obtained results of 78,74 cm from the FAA method and 73,66 cm with the FAARFIELD software. The results of these two methods have a thickness greater than the current pavement condition of Pattimura airport, which is 68,58 cm. Therefore it is necessary to re-plan the thickness of the pavement so that it can accommodate aircraft movements at the planned age.